Referendum Democracy
XVIII, 277 p.
Keywords: As the referendum becomes a more regular component of decision making, it leaves few, if any, institutions, processes and values of democracy untouched. Political actors of all kinds - including political parties and interest groups - seek to use the referendum device to further their own objectives. The end result is a different kind of democracy than existed before. This book lays out the comparative research agenda on the impact of referendums on the practice of liberal democracy.